ISHIKAWA DIAGRAM APPLICATION AS A LEARNING MEDIUM FOR QUALITY MANAGEMENT AT A MEATBALL FACTORY IN BANDUNG - Siregar, Dhita Sari; Kurniati, Yeni; Setyawati, Amelya; Chaerani, Gita Mutiara Annisa; Syailendra, Kahfi (Four Son Scholarship, 2025)
Product quality is not merely a technical issue in the industrial sector but also an essential competency that needs to be understood in quality management education, particularly in vocational education and applied higher education. Contextual and industry-based case learning in quality management is required to enable learners to understand quality control concepts in an applied manner. This study aims to examine the application of the Ishikawa Diagram as a problem-based quality management learning medium through a case study of declining meatball product quality at a manufacturing plant in Bandung, West Java. The research method employs a Quality Control Circle (QCC) approach using the Ishikawa Diagram to identify the root causes of quality problems, supported by Total Plate Count (TPC) testing as empirical evidence. The results indicate that the Ishikawa Diagram is effective not only as an analytical tool but also as a quality management learning medium, as it helps learners systematically understand cause-and-effect relationships within the production process. The main findings reveal that deviations in drying time due to increased production volume were the dominant factor contributing to the decline in meatball quality. This study contributes to the development of quality management learning based on real industrial case studies and strengthens the integration of quality management theory with practical field applications in educational contexts.